Formulasi Penanganan Sanksi Pidana Kerja Sosial terhadap Pelaku Korupsi Berbasis Keadilan - Husin, Umar (Jurnal Penelitian Hukum De Jure, 2023)
Law enforcement agrees that if crimes are categorized as serious or light, the perpetrators will be sentenced to prison sentences. There is no exception for perpetrators of criminal acts of corruption. In fact, Law Number 1 of 2023 concerning the Criminal Code regulates social work crimes for perpetrators of corruption crimes. It is a question of what the ideal formulation of punishment should be for perpetrators of corruption crimes. The purpose of this writing is to obtain information related to the imposition of social work sanctions on perpetrators of corruption. The method used in this research is normative juridical. This research found that the application of social work criminal sanctions for perpetrators of crimes, especially corruption crimes, is part of fulfilling a sense of justice and respect for human rights. It also has an impact on reducing the number of convicts in correctional institutions. The government and DPR need to amend the Corruption Crime law so that it is in accordance with what is regulated in Law Number 1 of 2023 concerning the Indonesian Criminal Code, especially on article number 85